Do Institutions Affect Social Preferences? Evidence from Divided Korea - Kim, Byung-Yeon; Choi, Syngjoo; Lee, Jungmin; Lee, Sokbae; Choi, Kyunghui (Journal of Comparative Economics, 2017)
•We report experiments of social preferences with North Korean refugees and South Korean students.•We find a sharp disparity in distributional preferences between NK refugees and SK subjects.•NK refugees behave in a less self-interested manner and support the market economy and democracy less than SK subjects.•This finding of disparity in distributional preferences are robust against sample selection and potential confounding factors such as income differences. The division of Korea is a historic social experiment that randomly assigned ex ante identical individuals into two different economic and political institutions. About 70 years after the division, we sample Koreans who were born and raised in the two different parts of Korea to study whether institutions affect social preferences. We find that those from North Korea behave in a less self-interested manner and support the market economy and democracy less than those from South Korea. A follow-up study shows that social preferences did not change considerably in two years. We check robustness against sample selection and potential confounding factors such as income differences. Our findings indicate that preferences are rooted in institutions.